Sieci neuronowe dla danych symbolicznych : perceptron wielowarstwowy - Pełka, Marcin (Neural Networks for Symbolic Data : Multilayer Perceptron, 2009)
The aim of this paper is to present and compare methods that allow to classify symbolic data with application of multilayer perceptron. In the article, basic terms of neural networks and transformation methods of symbolic interval-valued variables are presented. The article presents and compares in the empirical part simulation experiment results based on artificial data generated with application of cluster.Gen procedure from cluster.Sim package for R software. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 223-230